2021
DOI: 10.1101/2021.06.13.448232
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Increased apoptotic priming of glioblastoma enables therapeutic targeting by BH3-mimetics

Abstract: IDH wild-type glioblastoma (GBM) is the most prevalent malignant primary brain tumour in adults. GBM typically has a poor prognosis, mainly due to a lack of effective treatment options leading to tumour persistence or recurrence. Tackling this, we investigated the therapeutic potential of targeting anti-apoptotic BCL-2 proteins in GBM. Levels of anti- apoptotic BCL-xL and MCL-1 were consistently increased in GBM compared with non- malignant cells and tissue. Moreover, we found that relative to their differenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…Previously, it was demonstrated that TRAIL receptor agonists have broad efficacy against GBM cells alone or in combination with sensitisers [35,[45][46][47][48][49]. Beyond GBM, the CNS is also a frequent secondary site for many cancer metastases, including lung cancer, breast cancer and melanoma, consequently leading to lower treatment responses and poor patient outcomes [50,51].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, it was demonstrated that TRAIL receptor agonists have broad efficacy against GBM cells alone or in combination with sensitisers [35,[45][46][47][48][49]. Beyond GBM, the CNS is also a frequent secondary site for many cancer metastases, including lung cancer, breast cancer and melanoma, consequently leading to lower treatment responses and poor patient outcomes [50,51].…”
Section: Discussionmentioning
confidence: 99%
“…The underlying reason for this toxicity is most likely because neuronal development and survival is based on BCL-XL activity ( 66 ). Additionally, navitoclax is almost impenetrable to the blood brain barrier, thus, the current drugs are not able to reach the brain parenchyma ( 67 ). Thus, despite the demonstrated senolytic effects of BCL-2 family inhibitors, their clinical translation is limited due to potential side effects, off-target effects on platelets and poor central nervous system (CNS) penetrance.…”
Section: Cellular Senescencementioning
confidence: 99%